Emotional Labour and Work-Family Conflict in Voice-to-Voice and Face-to-Face Customer Relations: A Multi-Group Study in Service Workers - Federica Emanuel; Lara Colombo; Stefania Santoro; Claudio G. Cortese; Chiara Ghislieri (Europe's Journal of Psychology, 2020)
Professions that involve interaction with customers entail great emotional effort: workers are required to show emotions different from their true feeling and they experienced emotional dissonance and verbal aggression from customers. These job demands can generate discomfort and the effects of emotional labour can “expand” in other life domains. The study investigated the relationship among emotional dissonance, customer verbal aggression, affective discomfort at work and work-family conflict, considering differences between two groups of service workers: call centre agents (CA; N = 507, voice-to-voice relation with customers) and supermarket cashiers (SC; N = 444, face-to-face relation with customers). Results showed that emotional dissonance and customer verbal aggression had a positive relationship with work-family conflict, the mediational role of affective discomfort emerged in both groups; different effects of job demands in subsamples appeared. Suggestions for organisations and work processes emerged in order to identify practical implications useful to support employees in coping with emotional labour and to promote well-being and work-family balance.